Development and validation of a simple high‐performance liquid chromatography analytical method for simultaneous determination of phytosterols, cholesterol and squalene in parenteral lipid emulsions. (19th September 2017) - Novak, Ana; Gutiérrez‐Zamora, Mercè; Domenech, Lluís; Suñé‐Negre, Josep M.; Miñarro, Montserrat; García‐Montoya, Encarna; Llop, Josep M.; Ticó, Josep R.; Pérez‐Lozano, Pilar
Abstract: A simple analytical method for simultaneous determination of phytosterols, cholesterol and squalene in lipid emulsions was developed owing to increased interest in their clinical effects. Method development was based on commonly used stationary (C18, C8 and phenyl) and mobile phases (mixtures of acetonitrile, methanol and water) under isocratic conditions. Differences in stationary phases resulted in peak overlapping or coelution of different peaks. The best separation of all analyzed compounds was achieved on Zorbax Eclipse XDB C8 (150 × 4.6 mm, 5 μm; Agilent) and ACN–H2 O–MeOH, 80:19.5:0.5 ( v /v/v). In order to achieve a shorter time of analysis, the method was further optimized and gradient separation was established. The optimized analytical method was validated and tested for routine use in lipid emulsion analyses.